All Days 1990
DOI: 10.2118/21106-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gel Strength as Related to Carrying Capacity of Drilling Fluids

Abstract: This paper was presented by an SPE Program Committee following review of Information contained in an abstract submitted by the author(s). Contents of the paper, as presented, have not been reviewed by the Society of Petroleum Engineers and are subject to correction by the author(s). The material, as presented, does not necessarily reflect any position of the or SPE, their officers, or members. Papers presented at SPE meetings are subject to publication review by editorial Committees of the IADC and SPE. Permis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As indicated in the graph, the low gel strengths observed from the Mud-2 especially at high temperatures were caused by the presence of salt ions in the mud suspension reducing the hydration capacity of the clay mineral. With the addition of alumina nanoparticle as low as 0.05 wt%, significant improvements were observed on both 10-second and 10-minute gel strengths to the more acceptable range to provide good carrying ability, i.e., 5 Pa as suggested by Machado et al, 1990. An increasing trend was also observed as the concentration of alumina increases.…”
Section: Figure 10 Results Comparison On the Plastic Viscosity And Yi...mentioning
confidence: 81%
See 1 more Smart Citation
“…As indicated in the graph, the low gel strengths observed from the Mud-2 especially at high temperatures were caused by the presence of salt ions in the mud suspension reducing the hydration capacity of the clay mineral. With the addition of alumina nanoparticle as low as 0.05 wt%, significant improvements were observed on both 10-second and 10-minute gel strengths to the more acceptable range to provide good carrying ability, i.e., 5 Pa as suggested by Machado et al, 1990. An increasing trend was also observed as the concentration of alumina increases.…”
Section: Figure 10 Results Comparison On the Plastic Viscosity And Yi...mentioning
confidence: 81%
“…In the field, they represent the shear stress required to breakdown the gel structure of the mud to restart the flow. They are Machado and Aragao, 1990, suggested that a gel strength of about 5 Pa is sufficient to suspend cutting and provide good carrying capacity. Low and flat gels over time are always favourable as they indicate a constant rate of gelation.…”
Section: Silica-added Mudsmentioning
confidence: 99%
“…However, excess values can cause pipe-sticking problems. Hence, optimization of the gel strength is essential for the design of a drilling fluid …”
Section: Results and Discussionmentioning
confidence: 99%
“…In drilling horizontal well with gas, the suspension of a cutting is mainly due to three forces: one acts downward due to gravity, another lifts upward due to buoyancy, and the third lifts upward again due to viscous friction around the particle in the vertical direction (Machado and Aragao, 1990).…”
Section: Appendixmentioning
confidence: 99%